Pengaruh Model Pembelajaran Inkuiri Terbimbing terhadap Keterampilan Geografi Siswa Kelas X SMA Panjura Malang - Elvada, Erisa; Sahrina, Alfi; Wulandari, Sri (Cetta: Jurnal Ilmu Pendidikan, 2025)
Geography skills are abilities that need to be mastered, because they are useful in understanding the relationship between humans and the environment and can train students to think systematically in dealing with environmental and social issues. The advantage of the inquiry learning model lies in its ability to stimulate students to think critically in analyzing phenomena while honing observation and data interpretation skills. This study aims to determine the effect of guided inquiry learning model on geography skills of grade X students of SMA Panjura Malang. This research applied pseudo-experimental method. The subjects were taken using random sampling technique with X2 class as the experimental class and X4 class as the control class. Data was collected using Post-Test Only Control Group Design. The results revealed that the average Post-Test of geography skills of experimental class students with guided inquiry treatment was higher (88.83) compared to the control class (71.33). The results of hypothesis testing using the Mann-Whitney U-Test method show the results of Sig. (2-tailed) of 0.000 <0.05, which indicates a significant difference in the Post Test scores of the two classes. Thus the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted, so it can be concluded that the application of guided inquiry model has a significant effect on the mastery of geography skills. This study also found that the investigation stage is the most dominant stage affecting geography skills.